1985
DOI: 10.1128/mcb.5.9.2389
|View full text |Cite
|
Sign up to set email alerts
|

The two alpha-tubulin genes of Chlamydomonas reinhardi code for slightly different proteins.

Abstract: Full-length cDNA clones corresponding to the transcripts of the two alpha-tubulin genes in Chlamydomonas reinhardi were isolated. DNA sequence analysis of the cDNA clones and cloned gene fragments showed that each gene contains 1,356 base pairs of coding sequence, predicting alpha-tubulin products of 451 amino acids. Of the 27 nucleotide differences between the two genes, only two result in predicted amino acid differences between the two gene products. In the more divergent alpha 2 gene, a leucine replaces an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(88 citation statements)
references
References 44 publications
2
86
0
Order By: Relevance
“…The motif TGTAA, considered to be a potential polyadenylation signal in C. reinhardtii (Silflow et al 1985), was found 18 bases upstream from the 3'-end and also at position 1,225 in the cDNA sequence.…”
Section: Isolation and Sequence Analysis Of The Aox1 Cdnamentioning
confidence: 99%
“…The motif TGTAA, considered to be a potential polyadenylation signal in C. reinhardtii (Silflow et al 1985), was found 18 bases upstream from the 3'-end and also at position 1,225 in the cDNA sequence.…”
Section: Isolation and Sequence Analysis Of The Aox1 Cdnamentioning
confidence: 99%
“…The 5Ј end of the RNA transcript extends at least 272 base pairs upstream of the putative start codon. A putative polyadenylation signal (TGTAA) for Chlamydomonas (Silflow et al, 1985) is located 207 base pairs downstream of the TAG stop codon. The UNI2 gene sequence is available at GenBank under the accession number EF675992.…”
Section: Cloning and Tagging The Uni2 Genementioning
confidence: 99%
“…Transcripts from all four genes appear to accumulate coordinately during flagellar regeneration (5,39,43), and sequence comparisons among these genes have revealed several conserved 5' flanking regions (4) as well as an intriguing homology among all the genes in one of their intervening sequences (38,43). These conserved sequences are potential control regions for the induction of tubulin mRNA synthesis during flagellar regeneration, but because tubulin is used by the cell in organelles other than the flagellum, such as the mitotic spindle, there is a possibility that these sequences function to regulate tubulin gene expression during cellular events other than the production of new flagella.…”
Section: Expression Of Radial Spoke and Dynein Genesmentioning
confidence: 99%